Metabolic engineering of Saccharomyces cerevisiae for production of fatty acid short- and branched-chain alkyl esters biodiesel. Issue 1 (December 2015) - Teo, Wei; Ling, Hua; Yu, Ai-Qun; Chang, Matthew
Abstract Background Biodiesel is a mixture of fatty acid short-chain alkyl esters of different fatty acid carbon chain lengths. However, while fatty acid methyl or ethyl esters are useful biodiesel produced commercially, fatty acid esters with branched-chain alcohol moieties have superior fuel properties. Crucially, this includes improved cold flow characteristics, as one of the major problems associated with biodiesel use is poor low-temperature flow properties. Hence, microbial production as a renewable, nontoxic and scalable method to produce fatty acid esters with branched-chain alcohol moieties from biomass is critical. Results We engineeredSaccharomyces cerevisiae to produce fatty acid short- and branched-chain alkyl esters, including ethyl, isobutyl, isoamyl and active amyl esters using endogenously synthesized fatty acids and alcohols. Two wax ester synthase genes (ws2 andMaqu_0168 fromMarinobacter sp. ) were cloned and expressed. Both enzymes were found to catalyze the formation of fatty acid esters, with different alcohol preferences. To boost the ability ofS. cerevisiae to produce the aforementioned esters, negative regulators of theINO1 gene in phospholipid metabolism, Rpd3 and Opi1, were deleted to increase flux towards fatty acyl-CoAs. In addition, five isobutanol pathway enzymes (Ilv2, Ilv5, Ilv3, Aro10, and Adh7) targeted into the mitochondria were overexpressed to enhance production of alcohol precursors. By combining these engineering strategies with high-cell-density fermentation, over 230 mg/L fatty acid short- and branched-chain alkyl esters were produced, which is the highest titer reported in yeast to date. Conclusions In this work, we engineered the metabolism ofS. cerevisiae to produce biodiesels in the form of fatty acid short- and branched-chain alkyl esters, including ethyl, isobutyl, isoamyl and active amyl esters. To our knowledge, this is the first report of the production of fatty acid isobutyl and active amyl esters inS. cerevisiae . Our findings will be useful for engineeringS. cerevisiae strains toward high-level and sustainable biodiesel production.